Research on borehole repair model and working parameters optimization of self-propelled rotary excavator - Wang, Mian; Guo, Pengyu; Dong, Wenxin; Yang, Fan (Frontiers in Earth Science, 2023)
The collapse or plugging of gas extraction borehole can result in partial or complete failure of the extraction function, affecting the efficiency of gas extraction and increasing project costs. The integrated friction coefficient k indicates the resistance of the borehole repair system per unit length. The current repairing methods are mainly self-propelled and rotary drilling technology, which ignores the influence of drilling angle and return water flow on integrated friction coefficient k. In this paper, wellbore repair model based on Newton 's variable mass law is established. The relationship between repair length and hydraulic parameters, wellbore parameters and pipeline parameters is derived. The system resistance test experiment is carried out to clarify the influence of well length, angle, backwater and movement speed on the integrated friction coefficient k. Main conclusions are as follows : the integral friction coefficient k is the key parameter of the repair model, the system resistance increases linearly with the increase of drilling repair distance. Backwater exerts backward thrust on the front end of the drill bit and the high-pressure hose, resulting in an increase in the integrated friction coefficient k, the increase of drilling angle and jet pressure can lead to the increase of backwater flow and the increase of integral friction coefficient k. The improved repair model can more accurately predict the maximum repair distance of self-propelled and rotary drill bits. At the repair distance of 104.7 m, the error between the repair value and the experimental value is 5.7 m, which verifies the feasibility of the application of drilling repair in self-propelled and rotary drilling technology.